PERSPEKTIF HUKUM INDONESIA TENTANG HAK ATAS LINGKUNGAN HIDUP - Putra, Yuda Virdana; Putra, Alif Arhanda (JURNAL AKTA YUDISIA, 2023)
AbstractThe reality is that the environment is increasingly damaged by human actions.The environment is positioned as an object of exploitation: Mining the earthwithout control, deforesting without compromise, polluting water withoutcontrol, and other arbitrary actions. Violations of environmental norms result indisasters, both natural and man-made, and have cost many human lives. Thedestruction of the environment by a few people or companies has causedsuffering and human rights violations to the largest section of humanity. Theright to the environment is a basic human right that has been attached tohumans by nature, namely the rights that humans have as humans, which is agift from God. The right to a good and healthy environment as a human right hasbeen regulated in Article 28 of the Universal Declaration of Human Rights(UDHR), African Charter on Human and People Rights, Article 21 (1);International Covenant on Economic, Social and Cultural Rights (ESCR), Article1 (2); UN Resolution 1803 (XVII), December 14, 1962; UN Resolution 3281(XXIX), December 12, 1974; Agenda 21 of the 1992 Rio de Janeiro Earth Summit.The right to a good and healthy environment in Indonesia has also beenregulated in the 1945 Constitution, MPR Decree No. XVII/MPR/1998, Law No.39/1999 on Human Rights, Law No. 32/2009 on Environmental Protection andManagement, and Law No. 40/2007 on Limited Liability Companies.Keywords: Indonesian Legal; Perspective; Right to the Environment